1988
DOI: 10.1073/pnas.85.23.9292
|View full text |Cite
|
Sign up to set email alerts
|

Reversion toward an earlier stage of differentiation and loss of polarity during progression of N-methyl-N-nitrosourea-induced rat mammary tumours.

Abstract: To work toward an understanding of the mechanisms of cancer progression, we have followed the changes in expression of several genes in rat mammary carcinomas during the development of invasion. Tumors were induced by N-methyl-N-nitrosourea and serially transplanted to isogeneic rats. Gene expression in individual cells was followed by immunofluorescence microscopy. We show that invading cells do not express the same genes as the primary tumor or normal adult mammary gland but are similar to the primitive mamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…The coordinated loss of BM around tumor cells and the lack of membrane polarity have been reported for N-methyl-N-nitrosourea-induced rat mammary tumors (45). In this study all normal luminal cultures showed basal expression of BM components and the normal primary cultures showed (46)(47)(48)(49).…”
Section: Discussionmentioning
confidence: 54%
“…The coordinated loss of BM around tumor cells and the lack of membrane polarity have been reported for N-methyl-N-nitrosourea-induced rat mammary tumors (45). In this study all normal luminal cultures showed basal expression of BM components and the normal primary cultures showed (46)(47)(48)(49).…”
Section: Discussionmentioning
confidence: 54%
“…24,25 Early investigations suggested that this feature was due to altered gene expression for basement membrane proteins rather than any heightened enzymatic matrix breakdown. 26 This is further supported by evidence that breast carcinoma cells exhibit a downregulation in the laminin-binding integrin subunits. 27,28 As well as biochemical signaling from the extracellular matrix, cell-cell signaling mechanisms coordinate to maintain epithelial polarity and differentiation.…”
Section: Mammary Gland Developmental Stagessupporting
confidence: 64%
“…Disruption of the basal lamina is a crucial event that occurs in early neoplastic invasion and is characterized by the loss or abnormal formation of the structure [7,8]. The altered basal lamina may be due to dissolution by secretion of proteases by the invasive cells [7] or a defective construction by either the altered production or deposition of its main components [9]. In addition, the continued production of some of the basal lamina components has been observed to confer an advantage to further stages of tumor progression.…”
Section: Introductionmentioning
confidence: 99%